The Drivers of Responsible Investment: The Case of European Pension Funds - Sievänen, Riikka (Journal of business ethics, 2013)
We investigate what drives responsible investment of European pension funds. Pension funds are institutional investors who assure the income of part of the population for a long period of time. Increasingly, stakeholders hold pension funds accountable for the non-financial consequences of their investments and many funds have engaged in responsible investing. However, it appears that there is a wide difference between pension funds in this respect. We investigate what determines pension funds’ responsible investments on the basis of a survey of more than 250 pension funds in 15 European countries in 2010. We use multinomial logistic regression and find that especially legal origin of the country, ownership of the pension fund and fund size-related variables are to be associated with pension funds′ responsible investment. For fund size, we establish a curvilinear relationship; especially the smallest and largest pension funds in the sample tend to engage with responsible investing.